HUBUNGAN PENGETAHUAN DENGAN TINDAKAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK USIA 11–12 TAHUN DI SDN 020583 KOTA BINJAI TAHUN 2016 - Irma Handayani (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Dental and oral health education is one of the efforts to improve dental and oral primary school age is the ideal age to train motor skills of a child. The purpose of this study was to determine the relationship between knowledge and actions about maintaining oral health in children aged 11-12 year SDN 020583 Binjai city year 2016. In this case the researcher took a type of correlation study which aims to reveal the relationship of knowledge with actions on maintaining dental and oral health in children aged 11-12 years. The sample in this study were students aged 11-12 years in SDN 020583 in the city of Binjai as many as 32 people the instruments used in this study were questionnaires containing 20 questions. Data is then analyzed in the form of table characteristics of the level of knowledge and behavior of the respondents then presented. The results of the study r count (0.581)> r table so that the alternative hypothesis is accepted there is no significant relationship, then there is a relationship of knowledge with actions about the maintenance of teeth and mouth in children aged 11-12 years in SDN 020583 in Bandung 2016. t count: in the results of this calculation show that the value of t count (18,182)> t table (2,042). If t count> t tables of alternative hypotheses are accepted, it means that there is a significant relationship, then there is a relationship of knowledge with actions on maintaining dental and oral health in children aged 11-12 years in SDN 020583 in the city of 2016Keywords: Knowledge, actions of the child's teeth and mouth